Investigation of Morinda citrifolia Activity Related Collagen Type II Synthesis Through Gene Expression - Unchaleeporn Ameamsri; Runglawan Sudmoon; Warin Wonok; Sanit Kaewdaungdee; Tawatchai Tanee; Arunrat Chaveerach (HAYATI Journal of Biosciences, 2023)
To extend plant benefits, three different concentrations of five Morinda citrifolia part was investigated on the collagen type II which is the primary collagen in human cartilage through the expression of the genes, COL2A1, COL-II and COLL2 regions in normal human dermal fibroblasts by qRT-PCR method. The results showed that 1) fibroblasts cultured in the presence of M. citrifolia extracts produced many times more collagen type II gene expression than control cells depending on the plant parts and concentrations, 2) the expression levels of the collagen type II gene stimulated by all fruit parts yields the higher percentages than leaves. Next, Morus alba leaf extract at a concentration expected to be a precursor protein source for collagen synthesis, working together with M. citrifolia stimulation, was added to the selected concentration indicating high expression in the M. citrifolia fruit experiments. The result showed various gene expression levels depended on the kind of gene and fruit part. Therefore, M. citrifolia fruits can benefit the creation of collagen type II with or without M. alba. The M. citrifolia fruit can be further benefited in product production for both the elderly and young for maintaining the typical structure and function of the skin, tendon, and bone.